Determination of the plan of the A Famosa Fortress, Malaysia - Izani, M.; Bridges, A.; Razak, A. (2009)
The “A Famosa Fortress” is one of the oldest partially extant European buildings in Malaysia. It was built in 1511 by the Portuguese and went through several architectural developments and changes before being largely destroyed during the British occupation in 1824.With the subsequent overbuilding of the site by Melaka city today, it is impossible to fully reconstruct this fortress in its physical context.In this paper, we focus on determining the fortress layout based on various textual descriptions and old drawings and plans in preparation to building a detailed 3-D digital model.We have identified several important issues arising from the lack of any authoritative documentation.Such plans as exist not only differ in their depiction of the fort, but also use various ancient measurement systems. The paper gives examples of these problems and shows how a verifiable conjectural layout has been constructed.This is then compared against such archaeological evidence as is currently available. We are not aware of any previously published attempt to verify the consistency, similarity and integrity of the documentary data.